Pengaruh Pijat Panggung terhadap Produksi ASI Ibu Post Partum di Ruang Cempaka Room Ngudi Waluyo Wlingi Hospital - Sriyati Sriyati; Yeni Kartika Sari (STIKes Patria Husada Blitar, 2015)
Breast milk is an emulsion of fat in the protein solution, laktosa, and inorganic salts secreted by the mamary glands of the mother. The oxytocin hormone is a hormone that affects of lactation process. Oxytocin is up to the alveoli of the mammry myoepithelial cell contraction causes surrounding the mammary alveoli and lactiferous ducts. Back massage on cervical 5-6 until the bottom of the shoulder blade stimulate endorphins and oxytocin secretion and improves blood circulation breast area. The purpose of research to determine the effect of back massage on milk production an mothers post partum in cempaka’s room Ngudi Waluyo Wlingi Hospital November 2014. Design Quasi Experimental research with the design of the Control Group Pre-Test Post-Test Design with Non Random data retrieval with Consecutive Sampling (1 week) with total 24 population and total sample 20 respondents. Analysis data with two different Test Mean (T Test) Independent by using Paired Sample Test with H1 is accepted when the value of p < 0,05 and Independent Sample Test H1 is accepted when the value of p < 0,05. And research result Paired Sample Test the showed significant values (p) of 0,000 smaller than alpha 0,05. And there is influence of back massage on milk production before and after treatment. From the reserch result suggested all post partum mothers to do a back massage.